Supportive Environments for Care of Families and Children. Issue 3 (May 2015) - Gordin, Peggy
<x xml:space="preserve">Abstract</x> Three projects recently initiated at St. Louis Children's Hospital to create and enhance a supportive environment for the care of children and their families are shared.